Water-based polytetrafluoroethylene coating and preparation method thereof

By adding porous graphite fiber-molybdenum disulfide assembly and nanofiller to the aqueous polytetrafluoroethylene coating, the existing coatings have solved the problems of poor wear resistance, insufficient adhesion, poor corrosion resistance and prone to cracks in the coating, and achieved the goal of achieving The coating has significantly improved wear resistance, corrosion resistance and lubricating properties.

CN119144192BActive Publication Date: 2025-02-18XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411640893.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing water-based polytetrafluoroethylene coatings have problems such as poor wear resistance, insufficient adhesion, poor corrosion resistance, and prone to cracks in coatings, which cannot meet the requirements of high speed, high stress and strong corrosion of aviation vehicles in extreme environments.

Method used

By adding polytetrafluoroethylene emulsion, perfluoroalkoxyvinyl ether copolymer emulsion, binder, functional slurry, high temperature leveling agent, alcohol ester twelve, thickener to aqueous polytetrafluoroethylene coating and defoaming agent to form a functional slurry with porous graphite fiber-molybdenum disulfide assembly and nanofiller to improve the wear resistance, corrosion resistance and lubricating properties of the coating.

Benefits of technology

Significantly improve the wear resistance, corrosion resistance and lubricity of the aqueous PTFE coating, reduce the surface cracks of the coating, improve the critical crack thickness, and enhance the interface compatibility between the PTFE resin and the filler. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144192B_ABST
    Figure CN119144192B_ABST
Patent Text Reader

Abstract

The present disclosure provides a kind of water-based polytetrafluoroethylene coating and its preparation method, relates to the field of aerospace technology, the water-based polytetrafluoroethylene coating includes: polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high temperature leveling agent, alcohol ester twelve, thickener, defoamer; wherein, the functional slurry includes porous graphite fiber-molybdenum disulfide assembly and wear-resistant filler and composite dispersant; polytetrafluoroethylene emulsion is 20~35 parts by weight; perfluoroalkoxy vinyl ether copolymer emulsion is 5~15 parts by weight; binder is 5~10 parts by weight; functional slurry is 10~25 parts by weight; high temperature leveling agent is 0.5~1 parts by weight; alcohol ester twelve is 1~5 parts by weight. The water-based polytetrafluoroethylene coating provided by the present disclosure can effectively improve the wear resistance, lubrication and corrosion resistance of the coating, and significantly improve the interface compatibility between polytetrafluoroethylene resin and filler, reduce the surface cracks of the coating, and increase the critical cracking thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of aerospace technology, and in particular to a water-based polytetrafluoroethylene coating and a preparation method of the water-based polytetrafluoroethylene coating. Background Art

[0002] Aircraft need to face various harsh environmental conditions during operation, such as but not limited to extreme climates such as high temperature, low temperature, high humidity, salt spray, typhoon, heavy rain, ice, etc. In this scenario, in order to ensure that the aircraft can work normally in these complex environments and maintain its performance and reliability, it is necessary to apply a high-performance protective coating on the surface of the aircraft. Polytetrafluoroethylene (PTFE), as a perfluoropolymer, is one of the materials with the best chemical resistance among organic polymer materials. Water-based coatings with polytetrafluoroethylene as the main body are not only environmentally friendly, but also have excellent stain resistance, heat resistance, self-lubrication and electrical insulation properties, making them the first choice for protective coatings on the surface of aircraft.

[0003] However, current water-based polytetrafluoroethylene coatings have shortcomings such as poor wear resistance, insufficient adhesion, poor corrosion resistance, and coatings that are extremely prone to cracking. They are unable to cope with the extremely harsh high-speed, high-stress, and highly corrosive service environment of aircraft. Therefore, in order to improve the safety of aircraft during flight, it is necessary to develop water-based polytetrafluoroethylene coatings with higher performance such as wear resistance, corrosion resistance, and lubricity.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] In view of this, a water-based polytetrafluoroethylene coating and a method for preparing the water-based polytetrafluoroethylene coating are provided, thereby overcoming at least to a certain extent the problems of poor wear resistance, insufficient adhesion, poor corrosion resistance and easy cracking of the water-based polytetrafluoroethylene coating caused by the limitations and defects of the relevant technology.

[0006] According to one aspect of the present disclosure, a water-based polytetrafluoroethylene coating is provided, which comprises: polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high-temperature leveling agent, alcohol ester twelve, thickener, defoamer; wherein:

[0007] The weight portion of the polytetrafluoroethylene emulsion is 20 to 35 weight portions;

[0008] The weight portion of the perfluoroalkoxy vinyl ether copolymer emulsion is 5 to 15 weight portions;

[0009] The weight portion of the binder is 5 to 10 weight portions;

[0010] The weight of the functional slurry is 10-25 parts by weight; the functional slurry comprises a porous graphite fiber-molybdenum disulfide assembly, a wear-resistant filler and a composite dispersant; the wear-resistant filler is a nano filler;

[0011] The weight portion of the high temperature leveling agent is 0.5 to 1 weight portion;

[0012] The weight portion of the alcohol ester twelve is 1 to 5 weight portions;

[0013] The weight portion of the thickener is 0.2 to 0.5 weight portion;

[0014] The weight portion of the defoamer is 0.2 to 0.5 weight portion.

[0015] In an exemplary embodiment of the present disclosure, the length of the porous graphite fiber is 10-30 μm, and the porosity of the porous graphite fiber is 0.03-0.08 cm 3 / g.

[0016] In an exemplary embodiment of the present disclosure, the functional slurry is prepared by:

[0017] (1) using a homogenizer to disperse the porous graphite fibers in an aqueous solution containing polyvinyl pyrrolidone and ascorbic acid to obtain a first mixed solution, and adding sodium molybdate and thiourea in sequence while stirring the first mixed solution to obtain a second mixed solution;

[0018] (2) adjusting the pH value of the second mixed solution to 4-5, stirring the second mixed solution after the pH value is adjusted, transferring it to a reactor, and reacting it in the reactor at a hydrothermal temperature of 160-220° C. for 12-48 hours;

[0019] (3) After the reaction is completed, the reaction result corresponding to the second mixed solution after the pH value is adjusted is centrifuged and washed to obtain the porous graphite fiber-molybdenum disulfide assembly;

[0020] (4) Weigh 20-30 parts of the porous graphite fiber-molybdenum disulfide assembly, 5-15 parts of diatomaceous earth, 10-20 parts of nanofiller, 0.5-5 parts of composite dispersant, and 40-50 parts of water, and mix the porous graphite fiber-molybdenum disulfide assembly, diatomaceous earth, nanofiller, composite dispersant and water evenly by ball milling to obtain the functional slurry.

[0021] In an exemplary embodiment of the present disclosure, in the process of preparing the porous graphite fiber-molybdenum disulfide assembly, the mass ratio between the sodium molybdate and the porous graphite fiber is 1-3:1;

[0022] The mass ratio of the sodium molybdate to the thiourea is 0.9:1 to 1.5:1;

[0023] The amount of polyvinyl pyrrolidone added is 30% to 60% of the mass of the sodium molybdate;

[0024] The amount of ascorbic acid added is 18% to 72% by mass of the sodium molybdate, and the concentration of ascorbic acid is 0.01 to 0.06 mol / L;

[0025] The particle size of the diatomaceous earth is 400-800 mesh;

[0026] The nano filler includes at least one of titanium dioxide, chromium oxide and aluminum oxide, and the particle size of the titanium dioxide, chromium oxide and aluminum oxide is 200-800 meshes;

[0027] The composite dispersant is composed of polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution. In the composite dispersant, the mass ratio of the polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution is 1:1:1-1:2:2.

[0028] In an exemplary embodiment of the present disclosure, in the porous graphite fiber-molybdenum disulfide assembly, the molybdenum disulfide is a spherical particle, and the average particle size of the molybdenum disulfide is 3 μm;

[0029] In the process of preparing the porous graphite fiber-molybdenum disulfide assembly, the thiourea and ascorbic acid are used as synergistic reducing agents, and the polyvinyl pyrrolidone and ascorbic acid are used as synergistic surfactants.

[0030] In an exemplary embodiment of the present disclosure, the concentration of the polytetrafluoroethylene emulsion is 60 wt %, the average particle size of the polytetrafluoroethylene emulsion is in the range of 200 to 300 nm, and the pH of the polytetrafluoroethylene emulsion is in the range of 9 to 11;

[0031] The concentration of the perfluoroalkoxy vinyl ether copolymer emulsion is 50 wt %, the average particle size of the perfluoroalkoxy vinyl ether copolymer emulsion is in the range of 150-250 nm, and the pH of the perfluoroalkoxy vinyl ether copolymer emulsion is in the range of 9-11.

[0032] In an exemplary embodiment of the present disclosure, the binder includes an inorganic binder and an organic binder;

[0033] The inorganic binder includes at least one of sodium silicate, silica sol and aluminum sol;

[0034] The organic binder includes polyamide-imide and polyethersulfone;

[0035] In the binder, the mass ratio between the inorganic binder and the organic binder is 1:5 to 1:1.

[0036] In an exemplary embodiment of the present disclosure, the binder includes multiple types of silica sol, polyethersulfone and polyamideimide;

[0037] In the binder, the mass ratio between the inorganic binder composed of the silica sol and the organic binder composed of the polyamide-imide and polyethersulfone is 1:3;

[0038] In the organic binder, the mass ratio between the polyethersulfone and the polyamideimide is 2:1;

[0039] The polyethersulfone and polyamideimide are 25% solid content aqueous suspension.

[0040] In an exemplary embodiment of the present disclosure, the high temperature leveling agent includes modified polysiloxanes;

[0041] The thickener includes an alkali-swellable associative thickener;

[0042] The water-based polytetrafluoroethylene coating further comprises a pH regulator and water, wherein the pH regulator comprises at least one of sodium hydroxide, potassium hydroxide and ammonia water.

[0043] According to one aspect of the present disclosure, there is provided a method for preparing a water-based polytetrafluoroethylene coating according to any one of the above items, comprising:

[0044] Adding water, perfluoroalkoxy vinyl ether copolymer emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer to polytetrafluoroethylene emulsion in sequence to obtain the water-based polytetrafluoroethylene coating;

[0045] Before adding the thickener, the pH value needs to be adjusted to 8-9 by a pH adjuster; in the process of preparing the water-based polytetrafluoroethylene coating, the stirring speed is 600-1200 rpm.

[0046] In a water-based polytetrafluoroethylene coating provided in an exemplary embodiment of the present disclosure, on the one hand, since the water-based polytetrafluoroethylene coating is added with polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high-temperature leveling agent, alcohol ester twelve, thickener, and defoaming agent, the lubricity and corrosion resistance of the coating can be improved on the basis of improving the wear resistance of the coating formed by the water-based polytetrafluoroethylene; on the other hand, the interface compatibility between the water-based polytetrafluoroethylene resin and the filler can be improved, thereby achieving the purpose of reducing surface cracks in the coating and increasing the critical cracking thickness; on the other hand, the coating formed based on the water-based polytetrafluoroethylene coating can effectively improve the wear resistance, lubricity and corrosion resistance of the coating, and significantly improve the interface compatibility between the polytetrafluoroethylene resin and the filler, reduce surface cracks in the coating, and increase the critical cracking thickness.

[0047] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0049] Figure 1 The SEM image of the porous graphite fiber-molybdenum disulfide assembly involved in Example 1 according to the exemplary embodiments of the present disclosure is schematically shown.

[0050] Figure 2 The SEM image of a polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating described in Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.

[0051] Figure 3 The SEM image of a polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating described in Comparative Example 2 according to an exemplary embodiment of the present disclosure is schematically shown.

[0052] Figure 4 The SEM image of a polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating described in Comparative Example 3 according to an exemplary embodiment of the present disclosure is schematically shown.

[0053] Figure 5 The figure schematically shows an example of the test result of the friction coefficient according to Embodiment 1 in the exemplary embodiments of the present disclosure.

[0054] Figure 6 A schematic diagram shows a coating formed based on the water-based polytetrafluoroethylene coating obtained in Example 2 according to an exemplary embodiment of the present disclosure after being exposed to a salt spray environment for 680 hours.

[0055] Figure 7 Schematically showing a coating formed based on the water-based polytetrafluoroethylene coating obtained in Example 3 before and after Taber abrasion according to an exemplary embodiment of the present disclosure.

[0056] Figure 8 A schematic diagram shows a coating formed based on the water-based polytetrafluoroethylene coating obtained in Example 4 according to an exemplary embodiment of the present disclosure after being exposed to a salt spray environment for 680 hours.

[0057] Fig. 9 An exemplary diagram schematically shows an adhesion test result of a coating formed based on the water-based polytetrafluoroethylene coating obtained in Example 1 according to an exemplary embodiment of the present disclosure.

[0058] Fig.10 A schematic diagram of an actual object obtained after 88 hours in a salt spray environment is shown in an exemplary embodiment of the present disclosure, wherein a coating formed by a water-based polytetrafluoroethylene coating obtained in Comparative Example 1 is exposed to a salt spray environment.

[0059] Fig.11 An example diagram schematically shows the test results of the friction coefficient of a coating formed based on the water-based polytetrafluoroethylene coating obtained in Comparative Example 1 according to an exemplary embodiment of the present disclosure.

[0060] Fig.12 The SEM image of a coating formed based on the waterborne polytetrafluoroethylene coating obtained in Comparative Example 3 according to an exemplary embodiment of the present disclosure obtained after 168 hours in a salt spray environment is schematically shown. DETAILED DESCRIPTION

[0061] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.

[0062] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.

[0063] In the process of practical application, in order to improve the wear resistance, corrosion resistance, lubrication, light and heat properties of the coating formed by water-based polytetrafluoroethylene coating, corresponding functional fillers can be added to the water-based polytetrafluoroethylene coating. For example, in the relevant technical scheme, hydrophilic functional fillers can be added to the water-based polytetrafluoroethylene coating to enhance the mechanical and stability properties by enhancing the interface bonding with polytetrafluoroethylene. However, since this scheme has limited improvement on the comprehensive properties of the coating such as wear resistance, corrosion resistance, and lubrication, and the thickness of the polytetrafluoroethylene coating currently reported is mostly between 15 and 25 μm; therefore, insufficient coating surface thickness will lead to insufficient barrier capacity, which will provide a transport channel for water vapor and corrosive ions, seriously affecting the anti-corrosion performance of the coating and limiting its application on the surface of aviation aircraft.

[0064] Therefore, how to improve the wear resistance, corrosion resistance, lubricity and critical cracking thickness of water-based polytetrafluoroethylene coatings has become a technical problem that the entire industry needs to solve urgently. In order to solve this technical problem, the exemplary embodiment of the present disclosure provides a water-based polytetrafluoroethylene coating, which solves the above problems by cooperating with each other.

[0065] In an exemplary embodiment, the water-based polytetrafluoroethylene coating described in the exemplary embodiment of the present disclosure may include the following components: polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high-temperature leveling agent, alcohol ester twelve, thickener, and defoamer; wherein the weight parts of each component are: the weight part of polytetrafluoroethylene emulsion is 20 to 35 parts by weight; the weight part of perfluoroalkoxy vinyl ether copolymer emulsion is 5 to 15 parts by weight; the weight part of the binder is 5 to 10 parts by weight; the weight part of the functional slurry is 10 to 25 parts by weight; the weight part of the high-temperature leveling agent is 0.5 to 1 part by weight; the weight part of the alcohol ester twelve is 1 to 5 parts by weight; the weight part of the thickener is 0.2 to 0.5 parts by weight; and the weight part of the defoamer is 0.2 to 0.5 parts by weight.

[0066] In the above-mentioned water-based polytetrafluoroethylene coating, on the one hand, since the water-based polytetrafluoroethylene coating is added with polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high-temperature leveling agent, alcohol ester twelve, thickener, and defoaming agent; thus, the lubricity and corrosion resistance of the coating formed by the water-based polytetrafluoroethylene can be improved on the basis of improving the wear resistance of the coating; on the other hand, the interface compatibility between the water-based polytetrafluoroethylene resin and the filler can be improved, thereby achieving the purpose of reducing the surface cracks of the coating and increasing the critical cracking thickness; on the other hand, the coating formed based on the water-based polytetrafluoroethylene coating can effectively improve the wear resistance, lubricity and corrosion resistance of the coating, and significantly improve the interface compatibility between the polytetrafluoroethylene resin and the filler, reduce the surface cracks of the coating, and increase the critical cracking thickness.

[0067] Hereinafter, each component included in the water-based polytetrafluoroethylene coating described in the exemplary embodiment of the present disclosure will be explained and illustrated in detail.

[0068] In an exemplary embodiment, the functional slurry described above may include a porous graphite fiber-molybdenum disulfide assembly, a wear-resistant filler, and a composite dispersant; wherein the length of the porous graphite fiber described herein includes 10 to 30 μm, and the porosity of the porous graphite fiber includes 0.03 to 0.08 cm 3 / g; the wear-resistant filler described herein is a nanofiller. Further, the specific preparation process of the functional slurry described herein may include the following steps:

[0069] Step 1, using a homogenizer to disperse the porous graphite fiber in an aqueous solution containing polyvinyl pyrrolidone and ascorbic acid to obtain a first mixed solution, and adding sodium molybdate and thiourea in sequence while stirring the first mixed solution to obtain a second mixed solution;

[0070] Step 2, adjusting the pH value of the second mixed solution to 4-5, stirring the second mixed solution after the pH value is adjusted, transferring it to a reactor, and reacting it in the reactor at a hydrothermal temperature of 160-220° C. for 12-48 hours;

[0071] Step 3, after the reaction is completed, the reaction result corresponding to the second mixed solution after the pH value is adjusted is centrifuged and washed to obtain the porous graphite fiber-molybdenum disulfide assembly;

[0072] Step 4, weighing 20-30 parts of the porous graphite fiber-molybdenum disulfide assembly, 5-15 parts of diatomaceous earth, 10-20 parts of nanofiller, 0.5-5 parts of composite dispersant, and 40-50 parts of water, and mixing the porous graphite fiber-molybdenum disulfide assembly, diatomaceous earth, nanofiller, composite dispersant and water by ball milling dispersion to obtain the functional slurry.

[0073] In an exemplary embodiment, in the process of preparing the porous graphite fiber-molybdenum disulfide assembly, the mass ratio of sodium molybdate to porous graphite fiber is 1-3:1; the mass ratio of sodium molybdate to thiourea is 0.9:1-1.5:1; the amount of polyvinyl pyrrolidone added is 30%-60% of the mass of the sodium molybdate; the amount of ascorbic acid added is 18%-72% of the mass of the sodium molybdate, and the concentration of ascorbic acid is 0.01-0.06 mol / L; the particle size of diatomaceous earth is 400-800 mesh; the nano filler includes at least one of titanium dioxide, chromium oxide and aluminum oxide, and the particle sizes of titanium dioxide, chromium oxide and aluminum oxide are 200-800 mesh; the composite dispersant is composed of polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution, and in the composite dispersant, the mass ratio of polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution is 1:1:1-1:2:2.

[0074] In an exemplary embodiment, in the porous graphite fiber-molybdenum disulfide assembly, molybdenum disulfide is spherical particles, and the average particle size of molybdenum disulfide is 3 μm; in the process of preparing the porous graphite fiber-molybdenum disulfide assembly, thiourea and ascorbic acid are used as synergistic reducing agents, and polyvinyl pyrrolidone and ascorbic acid are used as synergistic surfactants.

[0075] The following will further explain and illustrate the specific components and specific preparation process of the functional slurry. Specifically, on the one hand, in the preparation process of the functional slurry, first, a homogenizer is used to disperse the porous graphite fiber in an aqueous solution containing polyvinyl pyrrolidone PVP and ascorbic acid, and sodium molybdate and thiourea are added in sequence under stirring, and the pH is adjusted to 4-5. After stirring evenly, it is transferred to a reactor for hydrothermal reaction at 160-220°C for 12-48 hours; after the reaction is completed, centrifugal washing is performed to obtain a porous graphite fiber-molybdenum disulfide assembly; then, 20-30 parts of the porous graphite fiber-molybdenum disulfide assembly, 5-15 parts of diatomaceous earth, 10-20 parts of nanofiller, 0.5-5 parts of composite dispersant, and 40-50 parts of water are weighed in parts by weight, and the functional slurry is obtained after being dispersed and mixed evenly by ball milling. Preferably, the dispersion method of the porous graphite fibers recorded above is homogenizer dispersion, the dispersion time is 3 to 10 min, and the rotation speed is 7000 to 15000 rpm; wherein, in the process of dispersing the porous graphite fibers, the specific dispersion time can be 6 min, and the specific rotation speed during the dispersion process can be 12000 rpm; it can also be set according to actual needs, and this example does not impose special restrictions on this; preferably, the mass ratio of sodium molybdate to porous graphite fibers recorded above is 1 to 3:1; the mass ratio of sodium molybdate to thiourea is 0.9:1 to 1.5:1; the amount of PVP added is 30 to 60% of the mass of sodium molybdate; the amount of ascorbic acid added is 18 to 72% of the mass of sodium molybdate, and the concentration is 0.01 to 0.06 mol / L.

[0076] More preferably, the mass ratio of sodium molybdate to porous graphite fiber is 2:1-3:1; the mass ratio of sodium molybdate to thiourea is 1:1-1.2:1; the amount of PVP added is 40-55% of the mass of sodium molybdate; the amount of ascorbic acid added is 30-50% of the mass of sodium molybdate, and the concentration is 0.03-0.05 mol / L; at the same time, in the process of pH adjustment, the specific value of the adjusted pH is 4-5, and the pH adjuster used is 5-15 wt% hydrochloric acid solution (the pH adjuster recorded here is different from the pH adjuster used in the preparation process of water-based polytetrafluoroethylene coating).

[0077] In an exemplary embodiment, during the pH adjustment process, the specific value of the adjusted pH may also include 4.5-5, and the pH adjuster used in the pH adjustment process may also be a 10 wt % hydrochloric acid solution.

[0078] In an exemplary embodiment, the hydrothermal reaction temperature required for the hydrothermal reaction in the reactor is 160~220°C, and the reaction time is 12~48 h; of course, in order to further improve the accuracy of the functional slurry preparation process, the hydrothermal reaction temperature required for the hydrothermal reaction in the reactor can be set to 180~200°C, and the specific reaction time can be set to 18~24 h.

[0079] In an exemplary embodiment, in the above-described centrifugal washing process, the number of water washings of the porous graphite fiber-molybdenum disulfide assembly can be set to 3 to 5 times; at the same time, after the centrifugal washing is completed, the obtained porous graphite fiber-molybdenum disulfide assembly can be dried in a 60 to 80°C oven to obtain the required porous graphite fiber-molybdenum disulfide assembly. At the same time, in the obtained porous graphite fiber-molybdenum disulfide assembly, molybdenum disulfide is presented as spherical particles, and the average particle size of the spherical particles of molybdenum disulfide is 3 μm; further, in the process of preparing the porous graphite fiber-molybdenum disulfide assembly, thiourea and ascorbic acid can be used as synergistic reducing agents, polyvinyl pyrrolidone PVP and ascorbic acid as synergistic surfactants, and the synergistic regulation of reducing agents, surfactants and pH regulators is the key factor for the controllable spherical morphology and particle size of molybdenum disulfide.

[0080] In an exemplary embodiment, the weight parts of the components included in the functional slurry described above are: 20-30 parts of porous graphite fiber-molybdenum disulfide assembly, 5-15 parts of diatomaceous earth, 10-20 parts of nanofiller, 0.5-5 parts of composite dispersant, and 40-50 parts of water. At the same time, in order to further improve the specific performance of the functional slurry, the weight parts of the above components can also be configured as follows: 20-30 parts of porous graphite fiber-molybdenum disulfide assembly, 5-10 parts of diatomaceous earth, 15-20 parts of nanofiller, 2-5 parts of composite dispersant, and 40-50 parts of water. Further, the nanofiller described herein can be selected from a combination of one or more of titanium dioxide, chromium oxide, and aluminum oxide, with a particle size of 200-800 nm; or, the nanofiller used herein can be a combination of titanium dioxide and chromium oxide, with a mass ratio of 1:1, a titanium dioxide particle size of 300-700 nm, and a chromium oxide particle size of 500-800 nm. Further, the dispersant used herein is a combination of polyethylene glycol trimethyl nonyl ether (TMN-10), a maleic acid copolymer solution, and a polyacrylate ammonium salt solution, with a mass ratio of 1:1:1-1:2:2; and the mixing method of the components of the aqueous wear-resistant slurry described herein is ball milling dispersion mixing, with a rotation speed of 200-300 rpm and a ball milling time of 1-2 h.

[0081] Hereinafter, other components in the waterborne polytetrafluoroethylene coating except the functional slurry will be further explained and illustrated.

[0082] (1) Polytetrafluoroethylene emulsion. Specifically, the concentration of the polytetrafluoroethylene emulsion described above is 60 wt %, the average particle size of the polytetrafluoroethylene emulsion is in the range of 200-300 nm, and the pH of the polytetrafluoroethylene emulsion is in the range of 9-11.

[0083] (2) Perfluoroalkoxy vinyl ether copolymer emulsion PFA. Specifically, the concentration of the perfluoroalkoxy vinyl ether copolymer PFA emulsion described above is 50 wt%, the average particle size of the perfluoroalkoxy vinyl ether copolymer emulsion ranges from 150 to 250 nm, and the pH range of the perfluoroalkoxy vinyl ether copolymer emulsion is 9 to 11.

[0084] (3) Binder. Specifically, the binder described above may include an inorganic binder and an organic binder; that is, the binder is composed of an inorganic binder and an organic binder. Meanwhile, the inorganic binder described herein includes at least one of sodium silicate, silica sol and alumina sol; the organic binder described herein includes polyamideimide and polyethersulfone; and, in actual application, in the binder, the mass ratio between the inorganic binder and the organic binder is 1:5 to 1:1.

[0085] In a feasible example embodiment, the binder described herein may also directly include multiple types of silica sol, polyethersulfone and polyamideimide; at the same time, in the binder in this scenario, the mass ratio between the inorganic binder composed of the silica sol and the organic binder composed of the polyamideimide and polyethersulfone is 1:3; and, in the organic binder, the mass ratio between polyethersulfone and polyamideimide is 2:1; further, the polyethersulfone and polyamideimide used herein are 25% solid water suspensions.

[0086] (4) High temperature leveling agent: Specifically, the high temperature leveling agent described above may include modified polysiloxanes.

[0087] (5) Thickener: Specifically, the thickener described above may include an alkali-swellable associative thickener.

[0088] (6) pH adjuster and water. Specifically, the pH adjuster used in the water-based polytetrafluoroethylene coating includes at least one of sodium hydroxide, potassium hydroxide, and ammonia water. Alternatively, the pH adjuster used in the water-based polytetrafluoroethylene coating can be a 10 wt% sodium hydroxide solution.

[0089] (7) Defoaming agent: Specifically, the defoaming agent described above may be a polyether siloxane copolymer containing fumed silica.

[0090] The exemplary embodiment of the present disclosure also provides a method for preparing a water-based polytetrafluoroethylene coating. Specifically, the water-based polytetrafluoroethylene coating can be prepared by the following method: water, perfluoroalkoxy vinyl ether copolymer emulsion, functional slurry, binder, high-temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence to obtain the water-based polytetrafluoroethylene coating; wherein, before adding the thickener, the pH value needs to be adjusted to 8-9 by the pH regulator; in the process of preparing the water-based polytetrafluoroethylene coating, the stirring speed is 600-1200 rpm.

[0091] As described above, the polytetrafluoroethylene coating described in the exemplary embodiment of the present disclosure has the following beneficial effects: on the one hand, the exemplary embodiment of the present disclosure provides a method for preparing a porous graphite fiber and molybdenum disulfide assembly, which improves both the wear resistance and the lubrication performance of the coating compared to direct mixing of the two; on the other hand, the micro-nano pores on the surface of the graphite fiber and diatomaceous earth in the exemplary embodiment of the present disclosure can further improve the wear resistance and lubrication performance of the coating on the basis of offsetting external forces and collecting lubricating debris during friction and wear; on the other hand, the functional slurry provided in the exemplary embodiment of the present disclosure has good interfacial compatibility with the polytetrafluoroethylene resin, and the dense layer formed can effectively block the passage of corrosive media, thereby improving the anti-corrosion performance of the coating; further, the exemplary embodiment of the present disclosure uses three binders to synergistically improve the adhesion between the coating and the substrate. Interface interaction; on this basis, not only can hydrogen bonding and cross-linking occur between the inorganic adhesive and the filler, but the formed three-dimensional network can also wrap around the surface of the filler, thereby enhancing the interface interaction between the fillers; at the same time, hydrogen bonding interaction can be formed between the oxygen atoms in the polyethersulfone and the hydroxyl groups on the metal substrate, thereby enhancing the interface bonding force between the coating and the substrate; of course, the polyethersulfone and polyamide-imide composite can significantly improve the spreading performance of the coating, thereby improving the adhesion of the coating; further, the water-based polytetrafluoroethylene coating provided in the exemplary embodiment of the present disclosure, the components cooperate with each other, can effectively reduce the cracks on the coating surface, increase the critical cracking thickness, and significantly improve the corrosion resistance, wear resistance, and lubrication performance; based on this, the obtained water-based polytetrafluoroethylene coating can have good application prospects in the fields involved.

[0092] Hereinafter, the water-based polytetrafluoroethylene coating and its preparation process described in the exemplary embodiments of the present disclosure will be further explained and illustrated in conjunction with specific embodiments. Specifically:

[0093] Example 1

[0094] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0095] 35 parts of polytetrafluoroethylene emulsion;

[0096] PFA emulsion 10 parts;

[0097] 5 parts of adhesive;

[0098] 20 parts of functional slurry;

[0099] 0.5 parts of high temperature leveling agent;

[0100] Alcohol ester 12 3 parts;

[0101] Thickener 0.3 parts;

[0102] 0.5 parts of defoaming agent;

[0103] The binder is selected from 1 part of silica sol, 2 parts of polyethersulfone and 2 parts of polyamideimide, the high temperature leveling agent is selected from Sano SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from sodium hydroxide, and 10wt% sodium hydroxide is used to adjust the pH to 8.23, and the balance is water.

[0104] The preparation method of the functional slurry is as follows:

[0105] First, the preparation process of the porous graphite fiber-MoS2 assembly can be achieved as follows: 1.00 g PVP and 1.50 g ascorbic acid were weighed and dissolved in 180 mL aqueous solution, and 0.70 g porous graphite fiber (wherein the porous graphite fiber has a length of 25 μm and a porosity of 0.08 cm) was added under stirring. 3 / g), and dispersed for 6 min using a homogenizer at 12000rpm. Keep stirring, add 2.10 g sodium molybdate and 2.30 g thiourea in sequence, adjust the pH to 4.5 with 5 wt% hydrochloric acid solution, and stir at room temperature for 30 min. Then transfer to a high-temperature reactor (200 mL) lined with polytetrafluoroethylene and hydrothermally react at 180 °C for 24 h. After the reactor is cooled to room temperature with the furnace, it is centrifuged and washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h to obtain a porous graphite fiber-molybdenum disulfide assembly; the SEM of the obtained porous graphite fiber-molybdenum disulfide assembly can be specifically referred to Figure 1 As shown; at the same time, from Figure 1 It can be seen that the hydrothermal reaction product is an assembly of porous graphite fibers and molybdenum disulfide, and molybdenum disulfide is spherical particles with an average particle size of 3 μm.

[0106] Secondly, for the preparation process of functional slurry, under mechanical stirring conditions, 0.8 parts of polyethylene glycol trimethyl nonyl ether TMN-10, 0.8 parts of maleic acid copolymer solution BYK-190 and 0.8 parts of polyacrylate ammonium salt solution BYK-154 were added to 50 parts of water in sequence. After stirring for 10 minutes, the speed was increased to 1200 rpm, and 26 parts of porous graphite fiber-molybdenum disulfide assembly, 11.6 parts of diatomaceous earth (400 mesh), 4 parts of titanium dioxide (200 mesh), and 6 parts of chromium oxide (200 mesh) were added in sequence; then, after dispersing for 1 hour, the slurry was transferred to a grinding jar, and zirconium oxide ball milling beads with a particle size of 6 mm were added for ball milling. The speed was set to 250 rpm and the ball milling time was 1 hour; at the same time, the SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating described in the embodiment can be referred to Figure 2 shown.

[0107] Example 2

[0108] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0109] 20 parts of polytetrafluoroethylene emulsion;

[0110] PFA emulsion 15 parts;

[0111] 6 parts of adhesive;

[0112] 25 parts of functional slurry;

[0113] 1 part of high temperature leveling agent;

[0114] Alcohol ester 12 1 part;

[0115] Thickener 0.5 parts;

[0116] 0.4 parts of defoaming agent;

[0117] Among them, the binder is selected from 1 part of sodium silicate, 3 parts of polyethersulfone and 2 parts of polyamideimide, the high temperature leveling agent is selected from Sino SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from ammonia water, which is adjusted to 8.47 with ammonia water, and the balance is water.

[0118] The preparation method of the functional slurry can be as follows:

[0119] (1) The preparation process of the porous graphite fiber-MoS2 assembly can be achieved as follows: 0.54 g PVP and 0.32 g ascorbic acid are weighed and dissolved in 180 mL aqueous solution, and 0.88 g porous graphite fiber (wherein the porous graphite fiber has a length of 10 μm and a porosity of 0.03 cm) is added under stirring. 3 / g), using a homogenizer at 15000rpm for a dispersion time of 3 min. Keep stirring, add 1.76 g of sodium molybdate and 1.52 g of thiourea in sequence, adjust the pH to 4 with a 10 wt% hydrochloric acid solution, and stir at room temperature for 30 min. Then transfer it to a high-temperature reactor (200 mL) lined with polytetrafluoroethylene, and hydrothermally react at 220°C for 12 h. The reactor is cooled to room temperature with the furnace, centrifuged and washed 3 times with deionized water, and then dried in an oven at 80°C for 12 h to obtain a porous graphite fiber-molybdenum disulfide assembly. At the same time, the hydrothermal reaction product obtained based on this method is an assembly of porous graphite fibers and molybdenum disulfide, and molybdenum disulfide is spherical particles with an average particle size of 3 μm. Among them, the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained based on this embodiment is similar to the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained in Example 1, and no further description is given here.

[0120] (2) For the preparation process of the functional slurry, it can be obtained in the following manner: under mechanical stirring conditions, 0.1 parts of TMN-10, 0.2 parts of BYK-190 and 0.2 parts of BYK-154 are added to 44.5 parts of water in sequence, and the speed is increased to 1200 rpm after stirring for 10 minutes, and 30 parts of porous graphite fiber-molybdenum disulfide assembly, 5 parts of diatomaceous earth (800 mesh), 10 parts of titanium dioxide (300 mesh), and 10 parts of chromium oxide (800 mesh) are added in sequence. After dispersion for 1 hour, the slurry is transferred to a grinding jar, and 6 mm zirconium oxide ball milling beads are added for ball milling, the speed is set to 200 rpm, and the ball milling time is 2 hours. At the same time, the SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating obtained in this embodiment is similar to the SEM image of the polytetrafluoroethylene coating obtained in Example 1, and no further description is given here.

[0121] Example 3

[0122] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0123] 30 parts of polytetrafluoroethylene emulsion;

[0124] PFA emulsion 5 parts;

[0125] 10 parts of adhesive;

[0126] 10 parts of functional slurry;

[0127] 0.8 parts of high temperature leveling agent;

[0128] Alcohol ester 12 5 parts;

[0129] Thickener 0.2 parts;

[0130] 0.2 parts of defoaming agent;

[0131] Among them, the binder is selected from 5 parts of aluminum sol, 3 parts of polyethersulfone and 2 parts of polyamideimide, the high-temperature leveling agent is selected from Sino SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from potassium hydroxide, which is adjusted to 8.55 with 10 wt% potassium hydroxide, and the balance is water.

[0132] The preparation method of the functional slurry can be as follows:

[0133] (1) The preparation process of the porous graphite fiber-MoS2 assembly can be achieved as follows: 2.28 g PVP and 1.88 g ascorbic acid are weighed and dissolved in 180 mL aqueous solution, and 3.80 g porous graphite fiber (wherein the porous graphite fiber has a length of 30 μm and a porosity of 0.06 cm) is added under stirring. 3 / g), using a homogenizer at 7000rpm for a dispersion time of 10 min. Keep stirring, add 3.80 g of sodium molybdate and 2.58 g of thiourea in sequence, adjust the pH to 5 with a 15 wt% hydrochloric acid solution, and stir at room temperature for 30 min. Then transfer to a high-temperature reactor (200 mL) lined with polytetrafluoroethylene for a hydrothermal reaction at 160 °C for 48 h. The reactor is cooled to room temperature with the furnace, centrifuged and washed 4 times with deionized water, and then dried in an oven at 60 °C for 24 h to obtain a porous graphite fiber-molybdenum disulfide assembly. Among them, the hydrothermal reaction product obtained in this way is an assembly of porous graphite fibers and molybdenum disulfide, and molybdenum disulfide is spherical particles with an average particle size of 3 μm. At the same time, the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained based on this embodiment is similar to the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained in Example 1, and no further description is given here.

[0134] (2) For the preparation process of the functional slurry, it can be achieved in the following manner: under mechanical stirring conditions, 1 part of TMN-10, 2 parts of BYK-190 and 2 parts of BYK-154 are added to 40 parts of water in sequence, and after stirring for 10 minutes, the speed is increased to 1200 rpm, and 20 parts of porous graphite fiber-molybdenum disulfide assembly, 15 parts of diatomaceous earth (500 mesh), 10 parts of titanium dioxide (800 mesh), and 10 parts of alumina (200 mesh) are added in sequence. After dispersing for 1 hour, the slurry is transferred to a grinding jar, 6 mm zirconium oxide ball milling beads are added, and the speed is set to 300 rpm for 1 hour. At the same time, the SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating obtained in this embodiment is similar to the SEM image of the polytetrafluoroethylene coating obtained in Example 1, and no further description is given here.

[0135] Example 4

[0136] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0137] 30 parts of polytetrafluoroethylene emulsion;

[0138] PFA emulsion 5 parts;

[0139] 8 parts of adhesive;

[0140] 10 parts of functional slurry;

[0141] 0.8 parts of high temperature leveling agent;

[0142] Alcohol ester 12 5 parts;

[0143] Thickener 0.2 parts;

[0144] 0.2 parts of defoaming agent;

[0145] Among them, the binder is selected from 2 parts of silica sol, 4 parts of polyether sulfone and 2 parts of polyamide-imide, the high-temperature leveling agent is selected from Sano SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from potassium hydroxide, which is adjusted to 8.55 with 10 wt% potassium hydroxide, and the balance is water.

[0146] The preparation method of the functional slurry can be as follows:

[0147] (1) The preparation process of the porous graphite fiber-MoS2 assembly can be achieved as follows: 2.28 g PVP and 1.88 g ascorbic acid were weighed and dissolved in 180 mL aqueous solution, and 3.80 g porous graphite fiber (length 30 μm, porosity 0.06 cm) was added under stirring. 3 / g), using a homogenizer at 7000 rpm for a dispersion time of 10 min. Keep stirring, add 3.80 g of sodium molybdate and 2.58 g of thiourea in sequence, adjust the pH to 5 with a 15 wt% hydrochloric acid solution, and stir at room temperature for 30 min. Then transfer to a high-temperature reactor (200 mL) lined with polytetrafluoroethylene and hydrothermally react at 160 ° C for 48 h. The reactor is cooled to room temperature with the furnace, centrifuged and washed 4 times with deionized water, and then dried in a 60 ° C oven for 24 h to obtain a porous graphite fiber-molybdenum disulfide assembly. Among them, the hydrothermal reaction product obtained in this way is an assembly of porous graphite fibers and molybdenum disulfide, and molybdenum disulfide is spherical particles with an average particle size of 3 μm. At the same time, the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained based on this embodiment is similar to the SEM image of the porous graphite fiber-molybdenum disulfide assembly obtained in Example 1, and no further description is given here.

[0148] (2) For the preparation process of the functional slurry, it can be achieved in the following manner: under mechanical stirring conditions, 1 part of TMN-10, 2 parts of BYK-190 and 2 parts of BYK-154 are added to 40 parts of water in sequence, and the speed is increased to 1200 rpm after stirring for 10 minutes, and 20 parts of porous graphite fiber-molybdenum disulfide assembly, 15 parts of diatomaceous earth (500 mesh), 10 parts of titanium dioxide (200 mesh), and 10 parts of aluminum oxide (800 mesh) are added in sequence. After dispersing for 1 hour, the slurry is transferred to a grinding jar, and 6 mm zirconium oxide ball milling beads are added for ball milling, and the speed is set to 300 rpm for 1 hour. At the same time, the SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating obtained in this embodiment is similar to the SEM image of the polytetrafluoroethylene coating obtained in Example 1, and no further description is given here.

[0149] Comparative Example 1

[0150] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, water-based slurry, binder, high-temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0151] 35 parts of polytetrafluoroethylene emulsion;

[0152] PFA emulsion 5 parts;

[0153] 8 parts of adhesive;

[0154] 12 parts of aqueous slurry;

[0155] 0.5 parts of high temperature leveling agent;

[0156] Alcohol ester 12 2 parts;

[0157] Thickener 0.3 parts;

[0158] 0.3 parts of defoaming agent;

[0159] The binder is selected from 2 parts of silica sol, 4 parts of polyethersulfone and 2 parts of polyamideimide, the high temperature leveling agent is selected from Sano SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from sodium hydroxide, and 10wt% sodium hydroxide is used to adjust the pH to 8.15, and the balance is water.

[0160] Method for preparing aqueous slurry

[0161] Under mechanical stirring conditions, 5 parts of TMN-10 were added to 50 parts of water in sequence. After stirring for 10 min, the speed was increased to 1200 rpm, and 5 parts of porous graphite fiber, 15 parts of commercial molybdenum disulfide (average particle size 3 μm), 15 parts of titanium dioxide (200 mesh), and 10 parts of chromium oxide (400 mesh) were added in sequence. After dispersing for 1 h, the slurry was transferred to a grinding jar, and 6 mm zirconium oxide ball milling beads were added for ball milling. The speed was set to 250 rpm and the ball milling time was 2 h.

[0162] Comparative Example 2

[0163] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, water-based slurry, binder, high-temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0164] 30 parts of polytetrafluoroethylene emulsion;

[0165] PFA emulsion 7 parts;

[0166] 10 parts of adhesive;

[0167] 15 parts of aqueous slurry;

[0168] 0.8 parts of high temperature leveling agent;

[0169] Alcohol ester 12 4 parts;

[0170] Thickener 0.4 parts;

[0171] 0.5 parts of defoaming agent;

[0172] The binder is selected from 2 parts of silica sol, 5 parts of polyethersulfone and 3 parts of polyamideimide, the high temperature leveling agent is selected from Sano SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH adjuster is selected from sodium hydroxide, and 10wt% sodium hydroxide is used to adjust the pH to 8.60, and the balance is water.

[0173] Method for preparing aqueous slurry

[0174] Under mechanical stirring conditions, 1 part of TMN-10, 1.5 parts of BYK-190 and 1.5 parts of BYK-154 were added to 40 parts of water in sequence. After stirring for 10 minutes, the speed was increased to 1200 rpm, and 20 parts of commercially available molybdenum disulfide (average particle size 3 μm), 15 parts of diatomaceous earth (400 mesh), 15 parts of titanium dioxide (200 mesh), and 6 parts of chromium oxide (200 mesh) were added in sequence. After dispersing for 1 hour, the slurry was transferred to a grinding jar, and 6 mm zirconium oxide ball milling beads were added for ball milling. The speed was set to 250 rpm and the ball milling time was 1 hour. The SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating obtained in this embodiment can be referred to Figure 3 shown.

[0175] Comparative Example 3

[0176] Implementation Case Under mechanical stirring conditions, water, PFA emulsion, functional slurry, binder, high temperature leveling agent, pH adjuster, thickener and defoamer are added to the polytetrafluoroethylene emulsion in sequence and stirred evenly. Among them:

[0177] 35 parts of polytetrafluoroethylene emulsion;

[0178] PFA emulsion 5 parts;

[0179] 8 parts of adhesive;

[0180] Functional slurry 12 parts;

[0181] 1 part of high temperature leveling agent;

[0182] Thickener 0.3 parts;

[0183] 0.5 parts of defoaming agent;

[0184] The binder is selected from polyethersulfone, the functional slurry is prepared according to Example 1, the high temperature leveling agent is selected from Sino SN-2550, the thickener is selected from TT-935, the defoamer is selected from TEGO-904W, and the pH regulator is selected from sodium hydroxide, and 10wt% sodium hydroxide is used to adjust the pH to 8.42, and the balance is water; wherein, the SEM image of the polytetrafluoroethylene coating prepared based on the polytetrafluoroethylene coating obtained in this example can be referred to Figure 4 shown.

[0185] Further, the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 3 were prepared into coatings by spraying, with a spraying pressure of ≥0.3 MPa, a spray gun caliber of 1 mm, a spraying distance of 20 to 30 cm, and the wet film was placed in an oven at 380 ° C for curing for 10 to 25 min. The coating thickness was tested by an eddy current thickness gauge; the surface micromorphology of the coating was observed by SEM; the wear resistance of the coating was tested by a Taber tester, with a load of 1 kg, a rotation speed of 60 r / min, and a number of revolutions of 1000; the lubricity of the coating was tested by an MS-M9000 reciprocating friction and wear tester, with a friction load of 20 N, a sliding distance of 5 mm, a frequency of 0.5 Hz, and a friction time of 30 min; the adhesion between the coating and the substrate was tested by the Baige method; and the anti-corrosion performance of the coating in a neutral salt spray environment was tested by a salt spray tester. Among them, the obtained comparison results can be specifically shown in Table 1 below.

[0186] Table 1 is the experimental results of Examples 1 to 4 and Comparative Examples 1 to 3

[0187]

[0188] The test results of the friction coefficient of Example 1 in Table 1 can be found in the following figure. Figure 5 As shown, the actual picture of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 2 after 680 hours in a salt spray environment can be referred to Figure 6 As shown; the actual picture of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 3 before and after Taber wear can be referred to Figure 7 As shown; the actual picture of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 4 after 680 h in a salt spray environment can be referred to Figure 8 As shown; the adhesion test results of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 1 can be referred to the example diagram Fig. 9 As shown; at the same time, the example diagram of the adhesion test results of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 2, Example 3 and Example 4 is similar to the example diagram of the adhesion test results of the coating formed by the water-based polytetrafluoroethylene coating obtained in Example 1, and no further description is given here; the actual picture of the coating formed by the water-based polytetrafluoroethylene coating obtained in Comparative Example 1 after 88 hours in a salt spray environment can be referred to as shown in Figure 10; the example diagram of the test results of the friction coefficient of the coating formed by the water-based polytetrafluoroethylene coating obtained in Comparative Example 1 can be referred to Fig.11 As shown; the SEM image of the coating formed by the water-based polytetrafluoroethylene coating obtained in Comparative Example 3 after 168 h in a salt spray environment can be referred to Fig.12 As shown; at the same time, Fig.12It can be seen that the coating formed by the water-based polytetrafluoroethylene coating obtained in Comparative Example 3 has the problem of coating peeling after 168 hours in a salt spray environment, and corrosion pits exist on the surface of the substrate after the coating is peeled off.

[0189] Further, based on the above Table 1 and Figure 2-Figure 12 It can be known without a doubt that the water-based polytetrafluoroethylene coating recorded in the exemplary embodiments of the present disclosure effectively overcomes various shortcomings in the prior art, and thus the water-based polytetrafluoroethylene coating recorded in the exemplary embodiments of the present disclosure has a high industrial utilization value.

[0190] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0191] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0192] It should be understood that the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims. The description and embodiments are to be regarded as exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A water-based polytetrafluoroethylene coating, characterized in that: The water-based polytetrafluoroethylene coating comprises: polytetrafluoroethylene emulsion, perfluoroalkoxy vinyl ether copolymer emulsion, binder, functional slurry, high-temperature leveling agent, alcohol ester twelve, thickener, defoamer; wherein: The weight portion of the polytetrafluoroethylene emulsion is 20 to 35 weight portions; The weight portion of the perfluoroalkoxy vinyl ether copolymer emulsion is 5 to 15 weight portions; The weight portion of the binder is 5 to 10 weight portions; The weight portion of the functional slurry is 10 to 25 parts by weight; the functional slurry includes a porous graphite fiber-molybdenum disulfide assembly, a wear-resistant filler and a composite dispersant; the wear-resistant filler is a nanofiller; the functional slurry is prepared by the following method: (1) using a homogenizer to disperse the porous graphite fiber in an aqueous solution containing polyvinyl pyrrolidone and ascorbic acid to obtain a first mixed solution, and adding sodium molybdate and thiourea in sequence while stirring the first mixed solution to obtain a second mixed solution; (2) adjusting the pH value of the second mixed solution to 4 to 5, stirring the second mixed solution after the pH value is adjusted, and then transferring it to a reactor, and reacting it in the reactor at a hydrothermal temperature of 160 to 220° C. for 12 to 48 hours. h; (3) after the reaction is completed, the reaction result corresponding to the second mixed solution after the pH value is adjusted is centrifuged and washed to obtain the porous graphite fiber-molybdenum disulfide assembly; (4) weighing 20-30 parts of the porous graphite fiber-molybdenum disulfide assembly, 5-15 parts of diatomaceous earth, 10-20 parts of nanofiller, 0.5-5 parts of composite dispersant, and 40-50 parts of water, and mixing the porous graphite fiber-molybdenum disulfide assembly, diatomaceous earth, nanofiller, composite dispersant and water by ball milling dispersion to obtain the functional slurry; The weight portion of the high temperature leveling agent is 0.5 to 1 weight portion; The weight portion of the alcohol ester twelve is 1 to 5 weight portions; The weight portion of the thickener is 0.2 to 0.5 weight portion; The weight portion of the defoamer is 0.2 to 0.5 weight portion.

2. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: The length of the porous graphite fiber is 10-30 μm, and the porosity of the porous graphite fiber is 0.03-0.08 cm 3 / g.

3. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: In the process of preparing the porous graphite fiber-molybdenum disulfide assembly, the mass ratio between the sodium molybdate and the porous graphite fiber is 1-3:1; The mass ratio of the sodium molybdate to the thiourea is 0.9:1 to 1.5:1; The amount of polyvinyl pyrrolidone added is 30% to 60% of the mass of the sodium molybdate; The amount of ascorbic acid added is 18% to 72% by mass of the sodium molybdate, and the concentration of ascorbic acid is 0.01 to 0.06 mol / L; The particle size of the diatomaceous earth is 400-800 mesh; The nano filler includes at least one of titanium dioxide, chromium oxide and aluminum oxide, and the particle size of the titanium dioxide, chromium oxide and aluminum oxide is 200-800 meshes; The composite dispersant is composed of polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution. In the composite dispersant, the mass ratio of the polyethylene glycol trimethyl nonyl ether, maleic acid copolymer solution and polyacrylate ammonium salt solution is 1:1:1-1:2:

2.

4. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: In the porous graphite fiber-molybdenum disulfide assembly, the molybdenum disulfide is a spherical particle, and the average particle size of the molybdenum disulfide is 3 μm; In the process of preparing the porous graphite fiber-molybdenum disulfide assembly, the thiourea and ascorbic acid are used as synergistic reducing agents, and the polyvinyl pyrrolidone and ascorbic acid are used as synergistic surfactants.

5. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: The concentration of the polytetrafluoroethylene emulsion is 60 wt %, the average particle size of the polytetrafluoroethylene emulsion is in the range of 200-300 nm, and the pH of the polytetrafluoroethylene emulsion is in the range of 9-11; The concentration of the perfluoroalkoxy vinyl ether copolymer emulsion is 50 wt %, the average particle size of the perfluoroalkoxy vinyl ether copolymer emulsion is in the range of 150-250 nm, and the pH of the perfluoroalkoxy vinyl ether copolymer emulsion is in the range of 9-11.

6. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: The binder includes an inorganic binder and an organic binder; The inorganic binder includes at least one of sodium silicate, silica sol and aluminum sol; The organic binder includes polyamide-imide and polyethersulfone; In the binder, the mass ratio between the inorganic binder and the organic binder is 1:5 to 1:

1.

7. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: In the binder, the mass ratio between the inorganic binder composed of silica sol and the organic binder composed of polyamide-imide and polyethersulfone is 1:3; In the organic binder, the mass ratio between the polyethersulfone and the polyamideimide is 2:1; The polyethersulfone and polyamideimide are 25% solid content aqueous suspension.

8. The water-based polytetrafluoroethylene coating according to claim 1, characterized in that: The high temperature leveling agent includes modified polysiloxanes; The thickener includes an alkali-swellable associative thickener; The water-based polytetrafluoroethylene coating further comprises a pH regulator and water, wherein the pH regulator comprises at least one of sodium hydroxide, potassium hydroxide and ammonia water.

9. A method for preparing a water-based polytetrafluoroethylene coating according to any one of claims 1 to 8, characterized in that: include: Adding water, perfluoroalkoxy vinyl ether copolymer emulsion, functional slurry, binder, high temperature leveling agent, alcohol ester twelve, pH regulator, thickener and defoamer to polytetrafluoroethylene emulsion in order to obtain the water-based polytetrafluoroethylene coating; Before adding the thickener, the pH value needs to be adjusted to 8-9 by a pH adjuster; in the process of preparing the water-based polytetrafluoroethylene coating, the stirring speed is 600-1200 rpm.

Citation Information

Patent Citations

  • Water-based polyamide-imide anti-corrosion non-stick coating and preparation method thereof

    CN112759988A

  • Novel self-lubricating surface coating composition

    US20120294557A1